2006
DOI: 10.1111/j.1085-9489.2006.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve injuries following intramuscular injections: a clinical and neurophysiological study from Northwest India

Abstract: In developing countries, injections are frequently used to treat common ailments. Intramuscular injections (IMI) may damage peripheral nerves at the site of injection. Our objectives were to study the clinical features, neurophysiological findings, and outcome in patients with nerve injuries (NI) following IMI and to determine the factors affecting prognosis. We conducted a retrospective review of patients with NI following IMI, who were referred to our Neurophysiology Laboratory at Christian Medical College, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 16 publications
2
36
0
3
Order By: Relevance
“…Among them, 29 (9.4%) patients had a radial nerve injury. Pandian et al [17] identified 29 (43.9%) patients having suffered a radial nerve injury among the 66 intramuscular injection related nerve injury patients. Above two reports, radial nerve injury is the second most common lesion after sciatic nerve injury.…”
Section: Reportsmentioning
confidence: 99%
“…Among them, 29 (9.4%) patients had a radial nerve injury. Pandian et al [17] identified 29 (43.9%) patients having suffered a radial nerve injury among the 66 intramuscular injection related nerve injury patients. Above two reports, radial nerve injury is the second most common lesion after sciatic nerve injury.…”
Section: Reportsmentioning
confidence: 99%
“…25 It may show signs of acute denervation, presenting as a high insertional activity, positive spontaneous fibrillation, and sharp waves with low interference and recruitment in the affected muscles; alternatively it may show signs of chronic denervation with reinnervation, presenting with polyphasia, high amplitude, and a lowered interference pattern and recruitment in the affected muscles. 36,37 Compound muscle action potential amplitude, sensory nerve action potential amplitude and nerve conduction velocity can also be used in the diagnosis of SNII. 36 A motor nerve conduction study can be performed on the common peroneal and posterior tibial nerves, with electrodes placed on the extensor digitorum brevis and abductor hallucis longus muscles, respectively.…”
Section: Snii Diagnosismentioning
confidence: 99%
“…36,37 Compound muscle action potential amplitude, sensory nerve action potential amplitude and nerve conduction velocity can also be used in the diagnosis of SNII. 36 A motor nerve conduction study can be performed on the common peroneal and posterior tibial nerves, with electrodes placed on the extensor digitorum brevis and abductor hallucis longus muscles, respectively. A sensory nerve conduction study of the sural and superficial peroneal nerves can be performed, with averaging of the sensory nerve action potential.…”
Section: Snii Diagnosismentioning
confidence: 99%
“…Prognosen for full tilheling etter nerveskader er generelt dårlig. I en rapport beregnet man at kun 28 % oppnådde full tilheling (11 …”
Section: Intramuskulaer Administrasjonunclassified